One Drought and One Volcanic Eruption Influenced the History of China: The Late Ming Dynasty Mega‐drought. Issue 16 (21st August 2020) - Chen, Kefan; Ning, Liang; Liu, Zhengyu; Liu, Jian; Yan, Mi; Sun, Weiyi; Yuan, Linwang; Lv, Guonian; Li, Longhui; Jin, Chunhan; Shi, Zhengguo
Abstract: The late Ming Dynasty Megadrought (LMDMD) (1637–1643) occurred at the end of Ming Dynasty and is the severest drought event in China in the last millennium. This unprecedented drought contributed significantly to the collapse of the Ming Dynasty in 1644, casting profound impacts on Chinese history. Here, the physical mechanism for the LMDMD is studied. Based on paleoclimate reconstructions, we hypothesize that this drought was initially triggered by a natural drought event starting in 1637 and was then intensified and extended by the tropical volcanic eruption at Mount Parker in 1641. This hypothesis is supported by the case study of the Community Earth System Model‐Last Millennium Experiment archive as well as sensitivity experiments with volcanic forcing superimposed on natural drought events. The volcano‐intensified drought was associated with a decreased land‐ocean thermal contrast, a negative soil moisture response, and a weakening and eastward retreating West Pacific Subtropical High. Plain Language Summary: The collapse of the Ming Dynasty at 1644 and, in turn, the historical transition from the Ming Dynasty to Qing Dynasty significantly changed the Chinese history into a long period of conservative policy. The collapse of Ming Dynasty at 1644 is greatly associated with the late Ming Dynasty Megadrought (LMDMD) (1637–1643). In this study, based on paleoclimate reconstructions and climate modeling, we show that the LMDMD is triggered by a natural drought event and is then intensified and extended by the strong volcanic eruption at Mt. Parker in 1641. This "superposition" mechanism of LMDMD and the spatiotemporal characteristics of this drought are reproduced by our volcanic sensitivity experiments with volcanic forcing superimposed on natural drought events, and the results demonstrate that the explosion of Mt. Parker at the end of a natural drought event amplified and extended the drought for 3 years, generating the megadrought. The volcano‐prolonged drought is associated with the failure of East Asia Summer Monsoon (EASM), which is caused directly by the decreasing land‐ocean thermal contrast after the volcanic eruption and indirectly by negative soil moisture feedback as well as weakening and eastward retreating of the West Pacific Subtropical High (WPSH). Key Points: The late Ming Dynasty Megadrought (LMDMD) is triggered by a natural drought event in 1637 and is then intensified and extended by the strong volcanic eruption in 1641 Volcanic eruption superimposed on a drought triggered by internal variability can intensify drought conditions, such that the drought becomes severer than that triggered by internal variability or external forcing alone The intensification of LMDMD is related to the weakening of land‐ocean thermal contrast, the retreat of West Pacific Subtropical High, and the decrease of soil moisture after volcanic eruption